2009
DOI: 10.1109/tmag.2009.2020329
|View full text |Cite
|
Sign up to set email alerts
|

Bit Storage by 360$^{\circ}$ Domain Walls in Ferromagnetic Nanorings

Abstract: We propose a design for the magnetic memory cell which allows an efficient storage, recording, and readout of information on the basis of thin film ferromagnetic nanorings. The information bit is represented by the polarity of a stable 360• domain wall introduced into the ring. Switching between the two magnetization states is achieved by the current applied to a wire passing through the ring, whereby the 360• domain wall splits into two charged 180• walls, which then move to the opposite extreme of the ring t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…This yields the exchange length l ' 3.37 nm, the Bloch wall thickness L ' 12 nm, and the quality factor Q ' 0.08, as in Ref. 9. Then the parameters used in our simulations would correspond to a film of thickness d ' 5 nm, inner radius R 1 ' 120 nm, and outer radius R 2 ' 180 nm.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…This yields the exchange length l ' 3.37 nm, the Bloch wall thickness L ' 12 nm, and the quality factor Q ' 0.08, as in Ref. 9. Then the parameters used in our simulations would correspond to a film of thickness d ' 5 nm, inner radius R 1 ' 120 nm, and outer radius R 2 ' 180 nm.…”
Section: Resultsmentioning
confidence: 89%
“…The latter represents the original proposal of Ref. 9 for the considered design. We found that the 360 domain wall states have the lowest energy among all the metastable configurations and thus represent the ground states of the system within the considered topological class.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vortex state can have either clockwise (CW) or counterclockwise (CCW) circulation, which have degenerate energies in uniform applied fields. Nanorings have been proposed as data storage elements, [1][2][3][4][5][6][7][8][9] taking advantage of the stable equilibrium CW and CCW configurations with no stray field. Understanding and controlling the switching of nanorings is of fundamental interest and critical to progress towards data storage applications.…”
mentioning
confidence: 99%